ملخص الدراسة اليقظة العقلية وعلاقتها بالصمود النفسي لدى طلبة المرحلة الثانوية في مدينة الخمس (Comprehensive Journal of Science, 2026)
This study aimed to identify the level of mindfulness and its relationship with psychological resilience among secondary school students in the city of Al-Khums.The study sample consisted of (150) male and female students from the third year of secondary school (both scientific and literary tracks), equally distributed by gender, with (75) males and (75) females. The sample was selected from two secondary schools in Al-Khums: Al-Khums Central Secondary School (Jaber) and Al-Maraqib Secondary School (Al-Hafra).To achieve the objectives of the study, the descriptive analytical method was employed. Two instruments were applied: the first was the Five Facet Mindfulness Questionnaire developed by Baer et al. (2006), which consists of (39) items measuring five different dimensions of mindfulness. The secosecond instrument was the Psychological Resilience Scale developed by Al-Kurd and Abu Omrah (2022), which consists of four dimensions; the first dimension includes (12) items, the second (13) items, the third (14) items, and the fourth (15) items